Nexus Between Tourism Sector and Regional Original Revenue: Empirical Evidence from West Nusa Tenggara, Indonesia - I Nengah Agus Sukresna; Baiq Ismiwati (Journal of Enterprise and Development (JED), 2024)
Purpose: This study aims to determine the effect of the tourism sector on Regional Original Revenue (PAD) in West Nusa Tenggara Province (NTB) by examining factors such as the number of tourists, the number of tourist attractions, the number of hotels, room occupancy rates, and the number of restaurants.Method: This study employed a descriptive quantitative approach using panel data, processed with EViews 12. This study utilizes secondary data obtained from the Central Statistics Agency (BPS), the Tourism Office, and regional financial reports over an 11-year period.Result: The findings show that tourist numbers and attractions have a positive impact on PAD, while number of hotels, occupancy rates, and restaurant have an insignificant impact on regional revenue. These results suggest that enhancing tourism infrastructure and attracting more visitors are key to boosting local economic performance.Novelty: The novelty of this study lies in its focus on West Nusa Tenggara (NTB) as an emerging tourism destination. It analyzes the 2013–2023 period and includes the number of restaurants to assess the impact of culinary tourism, alongside region-specific factors such as hotels, attractions, and occupancy rates.